The contribution of human capital to the performance of Knowledge-Intensive Business Services - Borodako, Krzysztof; Berbeka, Jadwiga; Rudnicki, Michał; Łapczyński, Mariusz (Annals of Management and Organization Research, 2019)
Purpose: The purpose of this paper is to investigate the relation between human capital and the performance of the various types of knowledge-intensive business services (KIBS). Research Methodology: The analysis conducted on business services industry level took into account the role of education in knowledge transfer, a major factor enriching the KIBS industry. A conceptual framework based on cluster analysis (CA) and classification and regression trees (CART) was developed to analyse human capital, the main asset in the KIBS sector (according to the resource-based theory), and its relations with the performance of KIBS providers. Results: The results pointed to the significant differences between various types of knowledge-based services. Findings suggest that there could be applied additional approach to classifying the KIBS services into three clusters according to the business characteristics (including human capital). Our third cluster closely related to human capital (HC) and information and communication technologies (ICT) demonstrated the best business performance. The results confirmed that KIBS providers with high average remuneration and high wage growth dynamic noted over doubled performance indicator (measured as profit growth). In that group of KIBS providers were (a) Software and IT companies, (b) Temporary employment agency activities and (c) Other human resources provision. Limitations: Our analysis is based on statistical data gathered by a public entity covered 3125 firms aggregated into twenty service types, which limits the scope of the research questions. Contribution: This study contributes to the state of knowledge of the performance dynamics of the various business services. Keywords: Business Services (BS), Human Capital (HC), Performance, Knowledge, Education